Posttraumatic Growth After MDMA‐Assisted Psychotherapy for Posttraumatic Stress Disorder. Issue 2 (19th February 2020) - Gorman, Ingmar; Belser, Alexander B.; Jerome, Lisa; Hennigan, Colin; Shechet, Ben; Hamilton, Scott; Yazar‐Klosinski, Berra; Emerson, Amy; Feduccia, Allison A.
Abstract: 3, 4‐Methylenedioxymethamphetamine (MDMA)–assisted psychotherapy for posttraumatic stress disorder (PTSD) has been shown to significantly reduce clinical symptomatology, but posttraumatic growth (PTG), which consists of positive changes in self‐perception, interpersonal relationships, or philosophy of life, has not been studied with this treatment. Participant data ( n = 60) were pooled from three Phase 2 clinical studies employing triple‐blind crossover designs. Participants were required to meet DSM‐IV‐R criteria for PTSD with a score higher than 50 on the Clinician‐Administered PTSD Scale (CAPS‐IV) as well as previous inadequate response to pharmacological and/or psychotherapeutic treatment. Data were aggregated into two groups: an active MDMA dose group (75–125 mg of MDMA; n = 45) or placebo/active control (0–40 mg of MDMA; n = 15). Measures included the Posttraumatic Growth Inventory (PTGI) and the CAPS‐IV, which were administered at baseline, primary endpoint, treatment exit, and 12‐month follow‐up. At primary endpoint, the MDMA group demonstrated more PTG, Hedges' g = 1.14, 95% CI [0.49, 1.78], p < .001; and a larger reduction in PTSD symptom severity, Hedges' g = 0.88, 95% CI [−0.28, 1.50], p < .001, relative to the control group. Relative to baseline, at the 12‐month follow‐up, within‐subject PTG was higher, p < .001; PTSD symptom severity scores were lower, p < .001; and two‐thirds of participants (67.2%) no longer met criteria for PTSD. MDMA‐assisted psychotherapy for PTSD resulted in PTG and clinical symptom reductions of large‐magnitude effect sizes. Results suggest that PTG may provide a new mechanism of action warranting further study. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Crecimiento Postraumático después de la Psicoterapia Asistida por MDMA para el Trastorno de Estrés Postraumático CRECIMIENTO POSTRAUMÁTICO DESPUÉS DE LA PSICOTERAPIA ASISTIDA CON MDMA Se ha demostrado que la psicoterapia asistida con 3, 4‐metilendioximetanfetamina (MDMA)‐ para el trastorno de estrés postraumático (TEPT) reduce significativamente la sintomatología clínica, pero el crecimiento postraumático (CPT), que consiste en cambios positivos en la autopercepción, las relaciones interpersonales o la filosofía de vida, no se ha estudiado con este tratamiento. Datos del participante (n = 60) se combinaron de tres estudios clínicos de fase 2 que emplearon diseños cruzados de triple ciego. Los participantes debían cumplir con los criterios del DSM‐IV‐R para TEPT con una puntuación superior a 50 en la Escala de TEPT administrada por el médico (CAPS‐IV en su sigla en inglés), así como una respuesta inadecuada previa al tratamiento farmacológico y / o psicoterapéutico. Los datos se agruparon en dos grupos: un grupo de dosis de MDMA activa (75‐125 mg de MDMA; n = 45) o placebo / control activo (0‐40 mg de MDMA; n = 15). Las medidas incluyeron el Inventario de crecimiento postraumático (PTGI en su sigla en inglés) y el CAPS‐IV, que se administraron al inicio, el punto final primario, la salida del tratamiento y el seguimiento a los 12 meses. En la evaluación al punto final primario, el grupo de MDMA demostró más PTG, g de Hedges = 1, 14, IC del 95% [0, 49, 1, 78], p <0, 001; y una mayor reducción en la gravedad de los síntomas del TEPT, g de Hedges = 0, 88, IC del 95% [‐ 0, 28, 1, 50], p <0, 001, en relación con el grupo de control. En relación con la evaluación inicial, a los 12 meses de seguimiento, la PTG intraindividual fue mayor, p <0, 001; las puntuaciones de gravedad de los síntomas del TEPT fueron más bajas, p <0, 001; y dos tercios de los participantes (67, 2%) ya no cumplían con los criterios de TEPT. La psicoterapia asistida con MDMA para el TEPT resultó en reducciones de PTG y síntomas clínicos de gran magnitud del efecto. Los resultados sugieren que la PTG puede proporcionar un nuevo mecanismo de acción que justifica un estudio adicional. 抽象: 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 JOTS‐19‐0080.R2 Gorman Posttraumatic Growth after MDMA‐Assisted Psychotherapy for Posttraumatic Stress Disorder Traditional Chinese 標題: 治療創傷後壓力症的MDMA輔助心理治療產生的創傷後成長 撮要: 過往研究顯示, 為治療創傷後壓力症(PTSD)的3, 4‐亞甲二氧甲基苯丙胺 (簡稱「MDMA」) 輔助心理治療, 能顯著減輕患者的臨床症狀。可是, 過往研究並未有檢視這種治療裡的創傷後成長 (PTG), 其包括自我感知、人際關係或人生哲學的正向改變。我們從3個採用三盲交叉試驗設計的第二階段臨床研究抽取樣本數據(n = 60)。樣本必須符合DSM‐IV‐R的PTSD準則, 並在臨床治療師執行的PTSD量表(CAPS‐IV)中分數超過50, 而且過往接受藥物和/或心理治療取得的成果不足。我們把數據綜合為兩組:活性MDMA藥物組(使用75–125 mg 的MDMA; n = 45), 和安慰劑/活性對照組(使用0–40 mg的MDMA; n = 15)。我們以創傷後成長量表(PTGI)與CAPS‐IV, 分別於基線、主要療效指標(primary endpoint)時點、終止治療時及終止治療12個月後, 對樣本進行測量。與對照組相比, MDMA藥物組在主要療效指標時點展現更高水平的PTG (Hedges' g = 1.14, 95% CI [0.49, 1.78], p < .001), PTSD症狀嚴重度亦有較大幅度的改善 (Hedges' g = 0.88, 95% CI [‐ 0.28, 1.50], p < .001) 。與基線相比, 樣本在終止治療12個月後, 個人的PTG水平較高 (p < .001), PTSD症狀嚴重度分數較低 (p < .001), 三分之二的樣本(67.2%)不再符合患PTSD。為治療PTSD的MDMA輔助心理治療能令樣本產生PTG, 帶來的臨床症狀改善效應量大。結果反映, PTG可能是新型療法的機制, 未來需有更多研究關注。 Simplified Chinese 标题: 治疗创伤后压力症的MDMA辅助心理治疗产生的创伤后成长 撮要: 过往研究显示, 为治疗创伤后压力症(PTSD)的3, 4‐亚甲二氧甲基苯丙胺 (简称「MDMA」) 辅助心理治疗, 能显著减轻患者的临床症状。可是, 过往研究并未有检视这种治疗里的创伤后成长 (PTG), 其包括自我感知、人际关系或人生哲学的正向改变。我们从3个采用三盲交叉试验设计的第二阶段临床研究抽取样本数据(n = 60)。样本必须符合DSM‐IV‐R的PTSD准则, 并在临床治疗师执行的PTSD量表(CAPS‐IV)中分数超过50, 而且过往接受药物和/或心理治疗取得的成果不足。我们把数据综合为两组:活性MDMA药物组(使用75–125 mg 的MDMA; n = 45), 和安慰剂/活性对照组(使用0–40 mg的MDMA; n = 15)。我们以创伤后成长量表(PTGI)与CAPS‐IV, 分别于基线、主要疗效指标(primary endpoint)时点、终止治疗时及终止治疗12个月后, 对样本进行测量。与对照组相比, MDMA药物组在主要疗效指标时点展现更高水平的PTG (Hedges' g = 1.14, 95% CI [0.49, 1.78], p < .001), PTSD症状严重度亦有较大幅度的改善 (Hedges' g = 0.88, 95% CI [‐ 0.28, 1.50], p < .001) 。与基线相比, 样本在终止治疗12个月后, 个人的PTG水平较高 (p < .001), PTSD症状严重度分数较低 (p < .001), 三分之二的样本(67.2%)不再符合患PTSD。为治疗PTSD的MDMA辅助心理治疗能令样本产生PTG, 带来的临床症状改善效应量大。结果反映, PTG可能是新型疗法的机制, 未来需有更多研究关注。